1979
DOI: 10.1159/000117684
|View full text |Cite
|
Sign up to set email alerts
|

The Principal Dimensions of Manifest Depression

Abstract: A factor analysis of a depression rating scale realized on a French sample of solely depressive patients gives evidence of 6 clearly defined factors having a particularly precise psychopathological meaning. The six factors, which correspond closely to those found in the American analysis of the same scale, span the full range of all principal depressive dimensions extracted from several other major depression rating scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Psychopathologists have also underscored that nonmelancholic depressions often entail anger, and that even during melancholic phases anger can emerge as an antidote against affective anesthesia characterized by the painful feeling of having no feelings [27]. Indeed, a close inspection of the psychiatric literature reveals that symptoms of anger, irritability, aggressiveness and hostility have indeed been observed in patients with depression, when the assessment has been performed with instruments exploring such symptoms [8, 9, 11, 28, 29, 30, 31]. Recently, it has been shown that when assessment instruments covering anger and irritability are used, these symptoms can be easily detected in many psychiatric disorders, particularly in depressed outpatients [2, 10, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathologists have also underscored that nonmelancholic depressions often entail anger, and that even during melancholic phases anger can emerge as an antidote against affective anesthesia characterized by the painful feeling of having no feelings [27]. Indeed, a close inspection of the psychiatric literature reveals that symptoms of anger, irritability, aggressiveness and hostility have indeed been observed in patients with depression, when the assessment has been performed with instruments exploring such symptoms [8, 9, 11, 28, 29, 30, 31]. Recently, it has been shown that when assessment instruments covering anger and irritability are used, these symptoms can be easily detected in many psychiatric disorders, particularly in depressed outpatients [2, 10, 32].…”
Section: Discussionmentioning
confidence: 99%
“…This might partly be ascribed to the use of specific rating scales for depression, which tend to put all depressions 'in the same basket'[2] and have been the object of some criticisms [3-6]. More recently, the use of comprehensive psychopathological rating scales exploring a wide range of symptoms has enabled several researchers to document substantial levels of anger, irritability, hostility and aggressiveness in a sizable portion of patients with unipolar depression [7-10]. Indeed, anger and aggression are prominent in depressed patients to a degree that may rival that of depression and anxiety [11], and anger is higher among patients with depression compared with patients with anxiety or somatoform disorders [12,13].…”
Section: Introductionmentioning
confidence: 99%